2015
DOI: 10.5812/cardiovascmed.25500
|View full text |Cite
|
Sign up to set email alerts
|

Single dose corticosteroid therapy after surgical repair of fallot’s tetralogy; A randomized controlled clinical trial

Abstract: Background:Inflammatory reaction can produce several complications after cardiac surgery. Many attempts have been made to reduce these complications; perioperative corticosteroid therapy is one of the simplest methods.Objectives:We conducted a randomized study to evaluate the efficacy of single dose methylprednisolone, prescribed after surgery, for reducing the complications. Repair of Tetralogy of Fallot was chosen as a homogenous large group for the study.Patients and Methods:One hundred children who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Dexamethasone injection before cardiopulmonary bypass reduces the postbypass inflammatory response in children, as measured by cytokine levels and clinical outcome [41]. Another study found that a single dosage of methylprednisolone (corticosteroid) has no effect on the clinical outcome after tetralogy of fallot repair [38]. Similarly, intraoperative methylprednisolone failed to show a meaningful reduction in the composite primary study endpoint's incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone injection before cardiopulmonary bypass reduces the postbypass inflammatory response in children, as measured by cytokine levels and clinical outcome [41]. Another study found that a single dosage of methylprednisolone (corticosteroid) has no effect on the clinical outcome after tetralogy of fallot repair [38]. Similarly, intraoperative methylprednisolone failed to show a meaningful reduction in the composite primary study endpoint's incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 267 records retrieved by the systematic search in PubMed and EMBASE, 10 studies met the inclusion criteria and included a total of 604 children (Table 8). [139][140][141][142][143][144][145][146][147][148] All studies were single centre. There were six retrospective cohort studies and four prospective, randomised, double-blind, placebo-controlled studies.…”
Section: Steroidsmentioning
confidence: 99%
“…However, some potential adverse effects may be associated with corticosteroids, for example, hyperglycemia, poor wound healing, infections, and poor neurodevelopmental outcomes (6)(7)(8). Several small, randomized, controlled studies in pediatric patients have investigated the effect of perioperative corticosteroids on the inflammatory biomarkers, clinical outcomes, and adverse events after congenital heart surgeries (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Nevertheless, the results were conflicted, resulting in the controversy over perioperative corticosteroids.…”
Section: Introductionmentioning
confidence: 99%